Legal Study on the Validity of Electronic Notarial Deeds in Indonesia: Regulatory Analysis and Practical Implications - Fahmi, Ardiansyah; Luthfi, Anas (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to evaluate the validity of electronic notary deeds in the context of Indonesian law, analyze their implementation challenges, and compare regulations with other countries that have adopted similar systems. The method used is a normative juridical approach with an analysis of various regulations, such as the Notary Position Law, the ITE Law, and the Government Regulation on Electronic Systems and Transactions. In addition, the study draws on the study of international literature and regulations, such as the eIDAS Regulation in the European Union, to offer a comparative perspective. Data analysis was carried out qualitatively through descriptive and comparative techniques. The findings show that regulations in Indonesia, while providing a basic foundation for electronic documents, still require more specific adjustments to accommodate the digitization of notary deeds. Key challenges include aspects of legal validity, digital security, and resistance to traditional legal culture. In contrast, the experiences of developed countries such as the European Union and Japan highlight the importance of reliable technological infrastructure and adaptive regulations to ensure successful implementation. The conclusion of the study emphasizes the need to harmonize national regulations with international standards as well as strengthen technological capacity and notary understanding of digital systems. The study recommends the development of a more integrated legal framework, improved digital security, and public and professional education to accelerate the transition to electronic notary deeds in Indonesia.